Rural development within the context of agricultural and socio-economic trends : the case of Finland - Voutilainen, Olli; Wuori, Olli (Versita, 2012)
Tämän artikkelin tavoitteena on selvittää maatalouden ja maaseudun sosioekonomisen kehityksen suhdetta Suomen maaseutualueilla vuodesta 1995. Analyysit perustuvat pääosin kuntatason tulo-, työllisyys- ja väestöindikaattoreihin. Tulokset osoittavat, että maatalouden ja maaseudun kehitys ja niiden välinen suhde vaihtelevat huomattavasti alueiden välillä. Lisäksi maatalouden aluerakenteet ja kehitys sekä niiden kytkökset maaseudun muuhun sosioekonomiseen kehitykseen ovat moniulotteisia. Yleisesti ottaen voidaan todeta, että maatalouden ja maaseudun kehityksen välillä ei ole merkittävää korrelaatiota. Tulokset tukevat räätälöidyn maatalous- ja maaseudun kehittämispolitiikan tarvetta erilaisille maaseutualueille

The aim of this article is to explore the relationship between agricultural and socioeconomic development in Finnish rural areas (later expressed as rural development) since 1995. The statistical analyses being employed are mainly based on municipal (i.e. LAU-2 level) income, employment and population indicators. The results show that agricultural and rural development and the relationship between them vary remarkably between regions. In addition, the regional structures and developments of agriculture and their links to rural development are multidimensional. In general, it can be stated that there is no significant correlation between agricultural and rural development. The results of this study support the demand for tailor-made agricultural and rural development policy for different rural regions.
Keywords: MA; maatalouden kehitys; maaseudun kehittäminen; agricultural development; rural development